Focus Groups: A Qualitative Research Technique in Market Research - Ivankovich-Guillén, Carmen Isabel (2011)
The focus groups are used in marketing research as a qualitative investigation tool, because of the possibility of interacting with the target group under study, whichallows to know and understand deeply the attitudes, needs, interests and motivations of the participants. Focus groups follow a rigorous development of the researchstages that start with the approach of the problem and conclude with oral and writing research presentation